A cointegration analysis of New Zealand's economic development, fossil fuel usage and transport emissions. Issue 4 (December 2022) - Sheng, Mingyue Selena; Sharp, Basil; Yi, Ming; Wen, Le; Suomalainen, Kiti
Highlights: An inverted U-shaped EKC existed between income and transport emissions in New Zealand. The turning point is US31, 070 in constant 2010 price for CO2 emissions from the transport sector. A unidirectional causality existed between economic development and transport-related emissions. A bidirectional causal relation existed between transport-related emissions and fossil fuel usage. More than half of the deviation from transport emission's long run equilibrium can be adjusted. Abstract: This study examines the relationship between New Zealand's (NZ) economic development, fossil fuel usage, and carbon dioxide (CO2 ) emissions from the transport sector from 1977 to 2013. The Autoregressive Distributed Lag (ARDL) bounds testing to cointegration procedure is conducted, followed by the Granger causality approach, to validate the hypothesis of the transport-energy environmental Kuznets curve (EKC). The empirical results of the study reveal an inverted U-shape between income and transport emissions for the sample period. The turning point is approximately US31, 070 in constant 2010 price, and NZ reached this income per capita level around 2002. Specifically, unidirectional causality between economic development and transport-related emissions was found in the short run, and it runs from economic development to transport emissions. Our findings deliver several policy implications. First, NZ's carbon reduction policy programs should focus more on transitioning from a carbon-based energy system to renewable energy. Second, push and pull measures to address carbon emissions reduction in the transport sector will not harm economic development. Given the important role that full cells play in decarbonising the heavy transport sector, future research should also incorporate the roll-out and deployment of hydrogen vehicles on the country's economic development, fossil fuel usage, and transport emissions.